Synthesis and characterization of biodegradable poly(xylitol sebacate dodecanoate)/ nano-hydroxyapatite composites for potential used in biomedical applications - Mohd. Sani, Noor Faezah (2013)
Xylitol-based polyesters such as poly(xylitol sebacate) (PXS) are said to be the best candidates for tissue engineering due to its tunable mechanical and degradation properties. In this study, dodecanedioic acid (DDA) was added into PXS as the additional monomer to increase the strength. Novel poly(xylitol sebacate dodecanoate) (PXSD) polymers was synthesized by using polycondensation method for potential used in tissue engineering. The starting materials for synthesizing PXSD are xylitol, sebacic acid (SA) and DDA and the ratio was varied (xylitol: SA: DDA), PXSD 1 (1:0.25:0.75) PXSD 2 (1:0.5:0.5) and PXSD 3 (1:0.75:0.25). The mixture synthesized at 120 °C for 24 hours under the present of nitrogen gas. After that it was further cured in an oven at 100 °C for 4 days. From the tensile test data, PXSD 1 was selected as the matrix to prepare PXSD/n-HA composite. Thermal stability and melting temperature slightly increased with the increasing in DDA ratio. Polymer crystallinity, mechanical properties such as tensile strength, percentage strain at break, Young’s modulus and degradation rate of the polymer was also controlled by the monomer ratio between SA and DDA. Increasing the DDA content resulted in highly ordered structure, improved mechanical properties and reduced erosion time. Much faster degradation rate was found in PXSD 3 compared to the more crystalline polymer of higher DDA content. Another objective was to investigate the effect of n-HA amount to the polymer properties and it was varied to 5, 10, 15 and 20 wt.%. By increasing the n-HA within the matrix, tensile strength and Young’s modulus were increased, but the percentage strain at break was reduced. The thermal properties showed no significant changes and distribution of the filler particles become well as the n-HA loadings were increased.